PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN PERTUMBUHAN PERUSAHAAN (GROWTH) TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN - Susanto, Edy (JURNAL STIE SEMARANG, 2016)
According Taswan and Soliha (2002), the high value of the company into the desires of the company, because the company's high value indicates prosperity shareholders also high. To achieve the objectives of the company, managers make investment decisions that resulted in a positive net present value (Jusriani and Siddiq, 2013). This study aims to examine empirically the effect of profitability, Managerial Ownership, and Corporate Growth (Growth) The Value Company With Capital Structure Mediation In Manufacturing Companies Listed on the Indonesia Stock Exchange Year 2009- 2012. The variables used in this study are Profitability, Managerial ownership, and Corporate Growth (Growth), Capital Structure, and Corporate Values population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2009 - 2011. the sample was selected using purposive sampling method in order to obtain as much as 87 issuers. The results of this study indicate that significantly influence the profitability and value of the company's capital structure, the company's growth has no significant effect on the capital structure, but significant effect on the value of the company. Managerial ownership does not affect the capital structure and corporate value. Capital structure does not significantly influence the value of the company.